Evolutionarily Conserved Roles for Blood-Brain Barrier Xenobiotic Transporters in Endogenous Steroid Partitioning and Behavior - Samantha J. Hindle; Roeben N. Munji; Elena Dolghih; Garrett Gaskins; Souvinh Orng; Hiroshi Ishimoto; Allison Soung; Michael DeSalvo; Toshihiro Kitamoto; Michael J. Keiser; Matthew P. Jacobson; Richard Daneman; et al. (Cell Reports, 2017)
Summary: Central nervous system (CNS) chemical protection depends upon discrete control of small-molecule access by the blood-brain barrier (BBB). Curiously, some drugs cause CNS side-effects despite negligible transit past the BBB. To investigate this phenomenon, we asked whether the highly BBB-enriched drug efflux transporter MDR1 has dual functions in controlling drug and endogenous molecule CNS homeostasis. If this is true, then brain-impermeable drugs could induce behavioral changes by affecting brain levels of endogenous molecules. Using computational, genetic, and pharmacologic approaches across diverse organisms, we demonstrate that BBB-localized efflux transporters are critical for regulating brain levels of endogenous steroids and steroid-regulated behaviors (sleep in Drosophila and anxiety in mice). Furthermore, we show that MDR1-interacting drugs are associated with anxiety-related behaviors in humans. We propose a general mechanism for common behavioral side effects of prescription drugs: pharmacologically challenging BBB efflux transporters disrupts brain levels of endogenous substrates and implicates the BBB in behavioral regulation. : Hindle et al. shed light on the curious finding that some drugs cause behavioral side-effects despite negligible access into the brain. These authors propose a unifying hypothesis that links blood-brain barrier drug transporter function and brain access of circulating steroids to common CNS adverse drug responses. Keywords: drug side effect mechanisms, central nervous system, blood brain barrier, behavior, toxicology, drug transporters, endobiotics, steroid hormones